Direct current cardioversion of atrial fibrillation in patients with left atrial appendage occlusion devices - Xie, Xin; Chen, Zijun; Li, Xiaorong; Yu, Jinbo; Zhou, Jian; Cheng, Dian; Wang, Xuecheng; Wu, Yizhang; Zhang, Baowei; Fan, Fenghua; Wang, Shuo; Yang, Bing (Frontiers in Cardiovascular Medicine, 2025)
Background and aimsData on the safety of direct current cardioversion (DCCV) in patients with left atrial appendage occlusion (LAAO) devices and its impact on thromboembolic prevention are limited. This study aimed to investigate the safety and efficacy of DCCV in patients with LAAO devices.MethodsThis single-center, ambispective cohort included patients undergoing one-stop procedures [LAAO combined with radiofrequency catheter ablation (RFCA)], where LAAO was performed first. DCCV was performed to restore sinus rhythm after LAAO. Patients were divided into the DCCV group and the no-DCCV group. Safety endpoints included DCCV-related death, device dislodgment, device embolization, and major bleeding events. Efficacy endpoints contained all-cause death, cardiovascular death, stroke/transient ischemic attack, and systemic embolism.ResultsA total of 196 patients (age 72.5 ± 7.4 years, 51.0% male) were enrolled, with 95 patients undergoing DCCV after LAAO. No DCCV-related death, device dislodgement, or device embolism was observed. At 12 months, the safety endpoints occurred in 3.2% of the DCCV group vs. 6.9% of the no-DCCV group (p = 0.238). Similarly, the efficacy endpoints were observed in 1.1% of the DCCV group vs. 4.0% of the no-DCCV group (p = 0.339). By performing pre- and post-DCCV transesophageal echocardiography (TEE) in the prospective cohort, a significant increase in device diameter at 45° and 90° (p = 0.044; 0.027), and an insignificant decline trend of peri-device leak and shoulder at 135° were noted (p = 0.051; 0.103).ConclusionsNo signal of excess risk was observed when performing DCCV in patients with LAAO devices. Tiny changes in device diameter after DCCV were noted on TEE at 45° and 90°, but these were not associated with adverse effects.